Story reading with incidental comprehension and memory: left hemisphere dominance - Vigliecca, Nora Silvana (Arquivos de Neuro-Psiquiatria, 2021)
Background: There are no studies on adults with unilateral brain lesions regarding story reading with incidental/implicit comprehension and memory, in which memory is only assessed through delayed recall. There is a need for validation of cerebral laterality in this type of verbal recall, which includes spontaneous performance (free or uncued condition (UC)), and induced-through-question performance regarding the forgotten units (cued condition (CC)). Objectives: To explore the effects of unilateral brain lesions, of oral reading with expression (RE) and comprehension (RC) on delayed recall of a story, as either UC or CC; and to validate the ability of UC and CC to discriminate the side of brain injury. Methods: Data were obtained from 200 right-handed volunteers, among whom 42 had left-hemisphere injury (LHI), 49 had right-hemisphere injury (RHI) and 109 were demographically-matched healthy participants (HP). Patients who were unable to read, understand or speak were excluded. Results: LHI individuals presented impairment of both UC and CC, in relation to the other two groups (non-LHI) with sensitivity and specificity above 70%. LHI and RHI individuals were not significantly different in RE and RC, but they were both different from HP in all the assessments except CC, in which RHI individuals resembled HP. Despite this lack of abnormality in RHI individuals during CC, about half of this group showed impairment in UC. Additionally, whereas RE had a significant effect on UC, the moral of the story (RC) had a significant effect on both UC and CC. Conclusions: The left hemisphere was dominant for this memory task involving implicit processing.
Keywords: Cognitive Dysfunction; Diagnosis; Narration; Neuropsychological Tests; Validation Study